Penentuan Awal Waktu Salat Wajib di Kota Sengkang dengan Menggunakan Metode Klasik dan Kontemporer - Sompa, Nurhalizah; Ilyas, Musfika (HISABUNA: Jurnal Ilmu Falak, 2020)
Abstract The main problem in this research is how to determine the beginning of prayer times using classical methods and contemporary methods in Sengkang City. The subject matter is further divided into 1) How to determine the initial prayer time in Sengkang City using the classical method? 2) How to determine the beginning of prayer times in Sengkang City using contemporary methods? The purpose of this study is to obtain information related to how the people of Sengkang city determine the start of prayer time both classically and contemporary. The purpose of this research is to obtain information related to how the people of Sengkang city determine the start of prayer time both classically and contemporary. Researchers make observations, interviews and documentation in order to collect accurate and relevant data for research. This type of research is a qualitative field research in which the researcher collects data directly by going directly to the field to obtain more efficient data, while the data mining technique uses reference books related to research titles, journals, previous theses and observation methods of interviews and documentation. . The results obtained in this study are the first people in the city of Sengkang in determining the time of obligatory prayers using classical methods such as natural phenomena, shadows of objects, animal sounds and using methods compiled by angregurutta H. Muhammad Yunus Martan. Second, the majority of people in the city of Sengkang use the decree of the Ministry of Religion of Wajo Regency, thus indirectly the community uses the contemporary method used by the Ministry of Religion of the District. Wajo, namely using the formula for determining prayer times and using applications for determining prayer times, one of which is a pro Muslim. Implications The research in this thesis is a matter of determining the initial time of the obligatory prayers which the public must understand well. As for the suggestions and hopes from the author, namely, to everyone who covers the issue of worship, especially from the Ministry of Religion and astronomy students to carry out socialization and counseling related to determining the initial time of compulsory prayer. Kata Kunci: Salat, Klasik, Kontemporer